2000
DOI: 10.1111/j.1540-8175.2000.tb01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inotropic Stimulation on Left Atrial Appendage Function in Atrial Myopathy of Chronic Atrial Fibrillation

Abstract: Atrial fibrillation (AF) leads to remodeling of the left atrium (LA) and left atrial appendage (LAA), resulting in atrial myopathy. Reduced LA and LAA function in chronic AF leads to thrombus formation and spontaneous echo contrast (SEC). The effect of inotropic stimulation on LAA function in patients with chronic AF is unknown. LAA emptying velocity (LAAEV) and maximal LAA area at baseline and after dobutamine were measured by transesophageal echocardiography in 14 subjects in normal sinus rhythm (NSR) and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…A small clinical study of the effect of dobutamine in patients with chronic AF reported a modest improvement in left atrial appendage function and a decrease in LASEC in 2 of 5 patients. 19 In the present study, isoproterenol resulted in a significant increase in LAAEV, returning stunned atrial mechanical function to magnitudes in excess of pre-RFA values (62% greater) with the disappearance of LASEC. To our knowledge, the disappearance of LASEC by pharmacological maneuvers has not previously been described in the human atrium.…”
Section: Effect Of Isoproterenol and Calciumsupporting
confidence: 52%
“…A small clinical study of the effect of dobutamine in patients with chronic AF reported a modest improvement in left atrial appendage function and a decrease in LASEC in 2 of 5 patients. 19 In the present study, isoproterenol resulted in a significant increase in LAAEV, returning stunned atrial mechanical function to magnitudes in excess of pre-RFA values (62% greater) with the disappearance of LASEC. To our knowledge, the disappearance of LASEC by pharmacological maneuvers has not previously been described in the human atrium.…”
Section: Effect Of Isoproterenol and Calciumsupporting
confidence: 52%
“…9 The development of a therapy for AF-induced atrial contractile dysfunction with positive inotropic drugs has been hampered by the limited efficacy and low safety of these compounds. In some studies, isoprenaline 10 and dobutamine 11 showed only very limited effect on atrial contraction in patients after cardioversion of AF. In another study, dobutamine and intravenous administration of Ca 2ϩ nearly restored atrial contraction, but these drugs, given for days to weeks, may cause arrhythmias and ventricular cardiomyopathy, obviously limiting their use in the clinical setting of AF.…”
Section: Clinical Perspective P 1242mentioning
confidence: 99%
“…Use of positive inotropic drugs to improve atrial contractile function soon after cardioversion might reduce the risk of stroke during the post cardioversion period [5,6]. However, the limited efficacy and low safety of most of these compounds has limited the development of positive inotropic drugs to treat AF-induced atrial contractile dysfunction [7][8][9]. The ultrarapid delayed rectifier current (I Kur ) is an important determinant of repolarisation or refractoriness in the atria of dogs [10], pigs [11,12], goats [13], and humans [14].…”
Section: Introductionmentioning
confidence: 99%